Harvest of Terror - Strasburg, Toni (Debonair Productions, 2000)
Soros Documentary Fund The story of a man, a trained killer and one-time soldier now involved in humanitarian work in South Africa. A personal story of war and of what happens when war ends; of morals and landmines; of governments and individuals. It is a story about change and re-growth, of former enemies now working together and a man requesting amnesty from those that he used to persecute.